THE ROLE OF DEPARTEMENT OF TRANSFORTATION SIKKA DISTRICT TO OPTIMIATION OF THE FUNCTION OF LOKARIA TERMINAL, KANGAE SUBDISTRICT - Maria Nona Isa; Danar Aswim (Institut Pendidikan Indonesia, 2023)
This stud aims to determine the etent of the role of the Department of Transportation in ptimiing the unctions of Pulic Transport Terminals at okaria Terminal angae District and hat constraints are eperienced the Department of Transportation in optimiing the function of the terminal. This stud uses a descriptie ualitatie approach. The data sources used are primar data sources and secondar data sources. Informants inoled in this stud ere at the Sikka District Transportation Serice section of the Traffic and road transport section and okaria Terminal Users. Data ollection Techniues used are seration Interie and Documentation Techniues. Data analsis techniues include data reduction data reduction data displa data presentation and conclusion draingerification ithdraal of conclusions. The research results otained are efforts made the Department of Transportation such as initing the pulic and terminal users to maintain and care for eisting terminal facilities een though the are minimal coordination ith Terminal users entrepreneurs and driers to make optimal use of the terminal Increased aareness of Terminal users including ith motorccle tai driers to make the est use of the terminal location and plan to uild a ne terminal. oeer in carring out its role the Department of Transportation encounters ostacles or ostacles namel the limited numer of officers and the officials ho manage the terminal do not hae special knoledge of the terminal the location of the okaria Terminal hich does not accommodate all transportation there is no good cooperation eteen the Department of Transportation and other stakeholders the lack of support from polic makers. This research suggests that the goernment Department of Transportation proide infrastructure at the lokaria terminal increase the numer of emploees make a clear ork plan take a firm stand against iolations committed okaria Terminal users so that the can carr out their role optimall.